Prophylaxis in von Willebrand disease with von Willebrand factor concentrate and nonfactor therapies - Calvin B. van Kwawegen; Frank W.G. Leebeek (Research and Practice in Thrombosis and Haemostasis)
This manuscript summarizes the current status of prophylaxis and novel potential therapies to prevent bleeding in patients with von Willebrand disease (VWD). VWD is the most common inherited bleeding disorder, which is associated mainly with mucocutaneous bleeding and bleeding during surgical and dental interventions. More severely affected VWD patients, mostly those with type 2 and type 3, can also suffer from joint, muscle, and gastrointestinal bleeds. Most patients with mild and moderate VWD are treated with desmopressin. The majority of patients with type 2 and 3 are treated with von Willebrand factor concentrates, with or without factor VIII. These patients suffer from severe and frequent bleeds and may require regular infusions of von Willebrand factor concentrate to prevent bleeding, so-called prophylaxis, 1 to 3 times per week. In this article, we review the current status of prophylaxis in VWD. We will also discuss emerging treatments that may be used as long-term prophylaxis in patients with severe VWD. We include relevant new data on this topic that were presented during the 2024 International Society on Thrombosis and Haemostasis (ISTH) Congress.